Determinants of Capital Structure in Listed Insurance Companies in Nigeria - Bala, Sani Abdulrahman; Abatcha, Babagana Mallam (International Business and Accounting Research Journal, 2020)
This study investigates the determinants of capital structure in listed insurance companies in Nigeria for the period of thirteen years, from 2006-2018. Ex-post facto research design was adopted for this study. The population of the study is made up of the 28 insurance companies listed on the floor of the Nigerian Stock Exchange (NSE) as at 2018. Since the population is not too large, this study utilized census sampling technique to take all the population. The data used in this study were secondary data derived from annual reports of insurance companies that are listed on the NSE. The study used panel regression with respect to the use of Hausman specification test to determine the use of fixed or random effect model. The random effect regression result revealed that that firm size has insignificant positive effect on capital structure (CST) of listed insurance companies in Nigeria. The study showed a significant positive effect between age and CST of listed insurance companies in Nigeria. Based on the regression result, asset tangibility has insignificant negative effect on CST, the regression result shows that risk has insignificant positive effect on CST, while the study found that insurance growth has significant positive effect on CST of listed insurance companies in Nigeria. The study concludes that size, age, tangibility of asset, insurance risk and growth are determinants of CST of listed insurance companies in Nigeria. The study recommends that insurance companies should have a high consideration for the value of total asset when determining their capital mix. Also, insurance companies that have been incorporated for long should consider external financing likewise, insurance companies should not give fixed asset priority when considering their capital structure mix. Debt providers should seek for high return in order to hold the risk related to the bankruptcy and financial distress. Lastly, debt holders should require such return to hold the risk of agency conflicts with shareholders and management.